Psychological variables associated with happiness - Alarcón, Reynaldo (2000)
The results of a transcultural research in a sample of Peruvian college students regarding life satisfaction are reported. Life satisfaction is a concept used a a synonymous of happiness. The main problem of this research was to determine which of the variables were “better” predictors of happiness. The participants responded a battery of psychological tests of 171 items which explored six variables considered related to happiness. It was found that the variables “life satisfaction” and “frequency of positive affects” are highly and positive correlated (p<.01).